2017
DOI: 10.1016/j.quaint.2016.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Geobody architecture of continental carbonates: “Gazda” travertine quarry (Süttő, Gerecse Hills, Hungary)

Abstract: The Gazda quarry is one of the largest outcrops of the present-day Süttő travertine complex that is situated close to the town of Süttő (Hungary), in the Pannonian Basin. Sedimentological and petrographical analyses show that the Gazda travertine body is built out of phytohermal, wavy laminated, massive and flat laminated travertine lithofacies representing reed mound, slope, lacustrine and palustrine depositional environments, respectively. Based on petrographic analyses, the following three main textural fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
1
28
1
1
Order By: Relevance
“…The presence of Al, K and Fe can be related probably to the non-carbonate fraction mentioned above. Based on her studies of a large Pleistocene travertine complex at Süttő (NW of Budapest) Török (2018) and Török et al (2019) suggested that the majority of such trace elements were of detrital origin and they accumulated on the travertine surface as dust at times of temporary subaerial exposure. Temporary halts of the water-supply might have also resulted in dust (aerosol)-deposition on the surface of the Rudas travertine buildup, thus enhancing the non-carbonatic contamination of the subsequently precipitating travertine layer.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of Al, K and Fe can be related probably to the non-carbonate fraction mentioned above. Based on her studies of a large Pleistocene travertine complex at Süttő (NW of Budapest) Török (2018) and Török et al (2019) suggested that the majority of such trace elements were of detrital origin and they accumulated on the travertine surface as dust at times of temporary subaerial exposure. Temporary halts of the water-supply might have also resulted in dust (aerosol)-deposition on the surface of the Rudas travertine buildup, thus enhancing the non-carbonatic contamination of the subsequently precipitating travertine layer.…”
Section: Resultsmentioning
confidence: 99%
“…Other ranges that are comparable to the ones from Itaboraí Basin were verified in travertines from different sites in Italy (Gonfiantini et al ., 1968; Minissale et al ., 2002) and around the world, such as in the USA (Chafetz & Lawrence, 1994; Fouke et al ., 2000), Hungry (Török et al ., 2017), Tunisia (Teboul et al ., 2016), Germany (Usdowski et al ., 1979), China (Liu et al ., 2003) and Turkey (Özkul et al ., 2002; Uysal et al ., 2009; Kele et al ., 2011; Claes et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sajátos A Gerecsében a süttői édesvízi mészkőben a csomós mik rit szövet alapján definiálták a mikrobialit litofáciest, amit biofilmből való kalcitkiválásként értelmeztek (TÖRÖK et al 2017). Az egerszalóki hőforrás környezetében kivált édesvízi mészkő boundstone mikrofáciesében a szálas kalci mikroba és a csomós mikrit szöveti komponensek a jel - 11. ábra.…”
Section: Mikrobazátonyok Sajátos Sztromataktisz Előfordulások éS éDeunclassified